STEPPER MOTOR FOR USE IN ROTARY CONTROL ASSEMBLY OF INPUT DEVICE - GREENSLADE JASON (2019)
Embodiments of the subject matter described herein relates to a stepper motor for use in a rotary control assembly of an input device. The stepper motor includes a shaft; a magnet coupled to the shaftand operable to rotate with a rotation of the shaft, the magnet generating a first magnetic field; a first coil arranged on a rotational path of the magnet; and a first current source configured to supply a first current to the first coil to cause the first coil to generate a second magnetic field, a main direction of the second magnetic field being substantially parallel with a main direction ofthe first magnetic field while the magnet rotates and passes the first coil. 本文描述的主题内容的实施例涉及一种用于在输入设备的旋转控制组件中使用的步进电机。步进电机包括：轴；磁体，被耦合到轴并且可操作以随着轴的旋转而旋转，磁体生成第一磁场；第一线圈，被布置在磁体的旋转路径上；以及第一电流源，被配置为向第一线圈供应第一电流以使第一线圈生成第二磁场，在磁体旋转并且通过第一线圈时，第二磁场的主方向与第一磁场的主方向实质平行。